ANALISIS TINGKAT BRAND LOYALTY PADA PRODUK SHAMPOO MEREK “HEAD & SHOULDERS” - Johannes Marthin; Hatane Semuel (Institute of Research and Community Outreach - Petra Christian University, 2007)
This research is to know level of brand loyalty of shampoo Head & Shoulders and pyramid of brand loyalty, which consist of switcher buyer, habitual buyer, satisfied buyer, liking of the brand, and committed buyer of shampoo Head & Shoulders. Result of this research up on 1200 respondents indicate that: (1) Shampoo Head & Shoulders have consumer which at most at committed buyer, that is 91.25%, so that concluded nicely. (2) Percentage of switcher buyer, habitual buyer, satisfied buyer, liking of the brand, and committed buyer of shampoo Head & Shoulders successively is 18.50%, 42.08%, 79.67%, 86.60%, and 91.25%, so that pyramid of brand loyalty is like inversed pyramid. This matter indication that brand of Head & Shoulders have strong brand equity. Abstract in Bahasa Indonesia: Penelitian ini bertujuan untuk mengetahui tingkat brand loyalty konsumen atas shampoo merek Head & Shoulders dan mengetahui susunan piramida loyalitas, yang meliputi switcher, habitual buyer, satisfied buyer, liking of the brand, dan committed buyer atas shampoo merek Head & Shoulders. Hasil penelitian atas 1200 orang pelanggan menunjukkan bahwa: (1) Shampoo merek Head & Shoulders mempunyai konsumen yang paling banyak pada tingkat committed buyer, yaitu 91,25%, sehingga disimpulkan bagus. (2) Prosentase switcher buyer, habitual buyer, satisfied buyer, liking of the brand, dan committed buyer atas shampoo merek Head & Shoulders berturut-turut adalah 18,50%, 42,08%, 79,67%, 86,60%, dan 91,25%, sehingga susunan piramida loyalitas adalah seperti piramida terbalik. Hal ini mengindikasikan bahwa merek Head & Shoulders memiliki brand equity yang kuat. Kata kunci: brand loyalty, switcher, habitual buyer, satisfied buyer, liking of the brand, committed buyer.